Private sector climate resilient agriculture co-investment reaches over 237,000 farmers in East Africa - Recha, John W.M.; Osumba, Joab J.L.; Shilomboleni, Helena; Demissie, Teferi Dejene; Radeny, Maren A.O.; Byarugaba, Gloria; Wandera, Bright Asiimwe; Oggema, Sebastian; Keizer, Menno; Kasekende, Bashir; Solomon, Dawit (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Farming communities in Eastern Africa face immense challenges in the second decade of the 21st century, including a continuing population increase, rising food prices, declining soil fertility and crop yields, limited access to land, poor market access and high inflation (Kristjanson et al. 2012). Climate change is adding another challenge on top of these others. Africa’s climate is warmer than it was 100 years ago, and model-based projections of future greenhouse gas induced climate change for the continent project that this warming will continue, and in most scenarios, accelerate (Christensen et al. 2007).